Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1186/1476-9255-3-1
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of NF-κB activation and MMP-9 secretion by plasma of human volunteers after ingestion of maritime pine bark extract (Pycnogenol)

Abstract: French maritime pine bark extract (Pycnogenol ® ) displays a variety of anti-inflammatory effects in vivo. Aim of this study was to determine whether human plasma after oral intake of Pycnogenol contains sufficient concentrations of active principles to inhibit key mediators of inflammation. Blood samples from seven healthy volunteers were obtained before and after five days administration of 200 mg Pycnogenol per day. Plasma samples statistically significantly inhibited matrix metalloproteinase 9 (MMP-9) rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(50 citation statements)
references
References 21 publications
3
42
0
Order By: Relevance
“…Matrix-degrading metalloproteinases are key mediators of collagen degradation observed in photoaged human skin [23]. In vitro studies indicated that some metabolites from the pine bark extract identified in human urine exhibit inhibitory activity on lipopolysaccharide-induced secretion of matrix metalloproteinase 9 in human monocytes [24,25]. Also, in previous studies, oral supplementation of Pycnogenol® resulted in sufficient enrichment of active metabolites in human serum to moderately inhibit matrix metalloproteinase 9 secretion in human monocytes ex vivo [25].…”
Section: Effects Of Oral Pycnogenol® Intake On Skin Barrier Function/mentioning
confidence: 99%
“…Matrix-degrading metalloproteinases are key mediators of collagen degradation observed in photoaged human skin [23]. In vitro studies indicated that some metabolites from the pine bark extract identified in human urine exhibit inhibitory activity on lipopolysaccharide-induced secretion of matrix metalloproteinase 9 in human monocytes [24,25]. Also, in previous studies, oral supplementation of Pycnogenol® resulted in sufficient enrichment of active metabolites in human serum to moderately inhibit matrix metalloproteinase 9 secretion in human monocytes ex vivo [25].…”
Section: Effects Of Oral Pycnogenol® Intake On Skin Barrier Function/mentioning
confidence: 99%
“…Pycnogenol affects the transactivation capacity of NF-κB, thus reducing expression of the inflammatory genes regulated by this transcription factor 17. However, Pycnogenol does not prevent NF-κB from binding to DNA, suggesting that its mechanism of action is different from that of progesterone, which acts by preventing translocation of the activated NF-κB subunit to the cell nucleus and its consequent binding to DNA, where it will activate translation of genes such as Cox-2 that are involved in the inflammatory cascade 17.…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen hours after volunteers were given 300 mg or 200 mg of PBE, fifteen compounds from PBE were detected in the their plasma. 15,16 Maximum concentrations of four identified compounds in the plasma; catechin, caffeic acid, ferulic acid and taxifolin were 107 ng ml -1 , 17 ng ml -1 , 15 ng ml -1 and 33 ng ml -1 , respectively. Of those four substances, caffeic acid and catechin revealed antibacterial activity against A. baumannii clones in our research, but epicatechin, gallic acid and vanillin also contributed to the activity of PABE against both clones of A. baumanii, while ferulic acid slightly contributed to the activity of PABE against EU clone I.…”
Section: Resultsmentioning
confidence: 99%
“…In our research the tested in vitro concentrations of basic PABE components that showed antibacterial activity against A. baumannii were at least three orders of the magnitude higher than the concentration of substances found in plasma of patients after oral ingestion of the same quantity of PBE. 15,16 Therefore, the concern exists that the concentration of the bioactive substances in plasma of patients would not be high enough to treat bacteraemia, but since A. baumannii causes also skin and wound infections, 27,28,29 application of PABE in sufficient concentration in such cases is certainly possible. Except investigated basic substances, proanthocyanidins that were determined in PABE could have also contributed to the antibacterial activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation